Dynamic vs Static ABCG2 Inhibitors to Sensitize Drug Resistant Cancer Cells - Peng, Hui; Qi, Jing; Dong, Zizheng; Zhang, Jian-Ting (PLOS ONE, 2010)
Human ABCG2, a member of the ATP-binding cassette transporter superfamily, plays a key role in multidrug resistance and protecting cancer stem cells. ABCG2-knockout had no apparent adverse effect on the development, biochemistry, and life of mice. Thus, ABCG2 is an interesting and promising target for development of chemo-sensitizing agents for better treatment of drug resistant cancers and for eliminating cancer stem cells. Previously, we reported a novel two mode-acting ABCG2 inhibitor, PZ-39, that induces ABCG2 degradation in addition to inhibiting its activity. In this manuscript, we report our recent progresses in identifying two different groups of ABCG2 inhibitors with one inhibiting only ABCG2 function (static) and the other induces ABCG2 degradation in lysosome in addition to inhibiting its function (dynamic). Thus, the inhibitor-induced ABCG2 degradation may be more common than we previously anticipated and further investigation of the dynamic inhibitors that induce ABCG2 degradation may provide a more effective way of sensitizing ABCG2-mediated MDR in cancer chemotherapy.